Changes in cell density and morphology of selected cells of the ageing human dental pulp - Daud, H.; Nambiar, P.; Hossain, M.Z.; Rahman, M.R.; Bakri, M.M. (Wiley, 2014)
OBJECTIVES: The aim of this study was to determine the changes in cell density and morphology of selected cells of the ageing human dental pulp.